2016
DOI: 10.1002/chem.201602230
|View full text |Cite
|
Sign up to set email alerts
|

Trangmolins A–F with an Unprecedented Structural Plasticity of the Rings A and B: New Insight into Limonoid Biosynthesis

Abstract: The absolute stereostructures of trangmolins A-F (1-6), limonoids with three new and one known topologies of the rings A and B, were unambiguously determined by NMR spectroscopic investigations, single-crystal XRD analysis, and quantum-chemical electronic circular dichroism calculations. Compounds 1-3 contain a hexahydro-1H-inden-4-one motif, compound 4 comprises a hexahydro-2,6-methanobenzofuran-7-one cage, and compound 5 consists of a hexahydro-2H-2,8-epoxychromene scaffold. The C1-C30 linkage in 1-3 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…for [M + H] + , 541.2074). The similarities between the NMR spectroscopic data of 22 ( Table 7 and Table 8 ) and those of trangmolin F [ 16 ], containing a ( Z )-bicyclo[5.2.1]dec-3-en-8-one substructure, revealed their close structural resemblance. However, the 3- O -isobutyryl function in trangmolin F was replaced by an acetoxy group (δ H 2.17 s 3H; δ C 170.4 qC, 20.6 CH 3 ) in 22 , being unambiguously confirmed by HMBC cross-peaks between H-3/C-32 and H 3 -33/C-32 ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…for [M + H] + , 541.2074). The similarities between the NMR spectroscopic data of 22 ( Table 7 and Table 8 ) and those of trangmolin F [ 16 ], containing a ( Z )-bicyclo[5.2.1]dec-3-en-8-one substructure, revealed their close structural resemblance. However, the 3- O -isobutyryl function in trangmolin F was replaced by an acetoxy group (δ H 2.17 s 3H; δ C 170.4 qC, 20.6 CH 3 ) in 22 , being unambiguously confirmed by HMBC cross-peaks between H-3/C-32 and H 3 -33/C-32 ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 97%
“…X. moluccensis , a true mangrove tree, is mainly distributed in Bangladesh, India, Indochina, Malesia, and tropical Australia. Previous chemical investigations of X. moluccensis resulted in the isolation of more than 100 limonoids with diverse carbon skeletons, such as mexicanolide, phragmalin, gedunin, andirobin, and khayanolide compounds [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Limonoids with diverse skeletons from X. moluccensis revealed structural plasticity in the limonoid biosynthesis of this mangrove species.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, C‐2 was bound to C‐3, and C‐3 was bound to C‐30. Bringmann et al., reported trangmolin D, which was the first example having C‐3‐C‐30 connection in limonoids . These results indicated that 2 was an unprecedented limonoid with a 6,6,5,6,6 ring system.…”
Section: Figurementioning
confidence: 99%
“…Li et al reported A‐ and B‐ rings in limonoids are mutable, while C‐ and d ‐ rings are relatively conservative . There have been many limonoids with cleavage between C‐16 and C‐17 in the d ‐ring.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation